A Retrospective Study on Clinical Features and Visual Outcome of Patients Hospitalized for Ocular Trauma in Cangzhou, China - Xi Zhang; Yuqing Liu; Xiangning Ji; Yuanyuan Zou (Journal of Ophthalmology)
Purpose. To describe clinical features and to analyze visual outcome of ocular trauma in Cangzhou in 2012–2015, China. Methods. A retrospective study of ocular trauma cases admitted to Cangzhou Central Hospital from January 2012 till December 2015 was performed. Results. This study included a total of 507 eyes from 478 patients. Four hundred (83.7%) patients were male, with a male-to-female ratio of 5.1 : 1. Mean age was 43.6±18.3 years (5–95 years). The largest age group was 45–59 years old, followed by 30–44 years old, presenting two peaks of the age distribution and accounting for 28.5% and 27.2%, respectively. The most frequent type of injuries was work-related (194, 40.6%) followed by home-related (123, 25.7%). Initial visual acuity (VA) correlated with final VA (Spearman’s test, r=0.703, p=0.001). The Ocular Trauma Score also correlated with the final VA significantly (Spearman’s test, r=0.802, p=0.001). Conclusions. Susceptible population of eye injuries were middle- and young-aged working groups, and the proportion of males was higher. The leading two types of ocular trauma were work-related and home-related. Initial VA was a significant predictor of the final VA and the OTS possibly had predictive value in the final VA.